Completely Anonymous Certificateless Multi-Receiver Signcryption Scheme with Sender Traceability. (December 2022) - Li, Huixian; Wu, Chenhao; Pang, Liaojun
Abstract: Certificateless multi-receiver signcryption scheme provides an efficient solution for one-to-many communication applications and avoids the key escrow problem in the existing identity-based multi-receiver signcryption schemes. Many certificateless multi-receiver signcryption schemes have been proposed with various secure properties, such as receiver anonymity and sender anonymity. However, among the existing certificateless multi-receiver signcryption schemes with sender anonymity, there is no scheme considers the sender tracing functionality. Sender anonymity is vulnerable and contradicts with non-repudiation. The anonymous sender may disavow the illegal message he has sent, which compromises the non-repudiation, so there is a high desirability to provide a sender tracing functionality which can be execute under certain conditions to balance the sender anonymity and non-repudiation. Motivated by these concerns, a new certificateless multi-receiver signcryption scheme is proposed, which achieves completely anonymity and provides the sender tracing functionality. In the proposed scheme, the key generation center can cooperate with any authorized receiver to trace the anonymous sender, but neither of them can do it alone. In this case, sender anonymity and non-repudiation reach a certain degree of balance.